Pengaruh Fear Of Missing Out (FOMO),Kemajuan Teknologi, Pengetahuan Investasi Terhadap Minat Investasi Mahasiswa Dalam Berinvestasi di Pasar Modal Bagi Generasi Z - Shiwi Angelica Cindiyasari; Alif Miftahul Jannah (TECHNOBIZ : International Journal of Business, 2025)
This study aims to analyze the effect of Fear Of Missing Out (FOMO), Technological Advances, Investment Knowledgeon students' investment interest in investing in the capital market for generation z in Bandar Lampung. The populationused in this study were active students of the Faculty of Economics and Business (FEB) and students who had taughtCapital Market courses who were born in 1997-2022. The sampling technique used in this study was Purposive Sampling.The results of this study indicate that the variables of technological advances and investment knowledge have a positiveand significant effect on students' Investment Interest in the capital market. Meanwhile, the variable fear of missing out(FOMO) has no effect on students' investment interest in the capital market.